2014
DOI: 10.1590/s0100-736x2014000500008
|View full text |Cite
|
Sign up to set email alerts
|

Fibrose cardíaca associada à intoxicação por Amorimia septentrionalis em bovinos

Abstract: Eight cattle were necropsied. Tissues were collected from abdominal and thoracic cavities, besides brain and spinal cord. The clinical changes consisted in apathy, prolonged sternal recumbency, reluctance to move, fatigue, tachypnea, tachycardia and positive venous pulse. The animals that were forced to move showed instability, muscular tremors and then a single fall followed by vocalizations, paddling and death in 5-7 minutes. Macroscopic changes consisted in pulmonary edema, globular heart with whitish areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…Sodium monofluoracetate was not quantified in plant samples used in the experiment conducted by Silva et al (2017). In the present study, the amount of MF in the A. septentrionalis samples was 0.00074% ±0.00018 and, although at a lower concentration than that observed by Lee et al (2012) and Albuquerque et al (2014), which was 0.002% of MF in the plant leaves, was able to cause poisoning, most likely by the repeated ingestion of small doses.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Sodium monofluoracetate was not quantified in plant samples used in the experiment conducted by Silva et al (2017). In the present study, the amount of MF in the A. septentrionalis samples was 0.00074% ±0.00018 and, although at a lower concentration than that observed by Lee et al (2012) and Albuquerque et al (2014), which was 0.002% of MF in the plant leaves, was able to cause poisoning, most likely by the repeated ingestion of small doses.…”
Section: Discussioncontrasting
confidence: 73%
“…In the Brazilian northeastern semi-arid region, mainly in the states of Ceará, Paraíba, and Pernambuco (Albuquerque et al 2014), poisoning with Amorimia septentrionalis is the most known, widespread and important cause of sudden death in ruminants (Duarte et al 2013). There are reports of poisoning outbreaks by this plant in sheep and goats in the state of Paraíba, with poisoning occurring mainly at the beginning of the rainy season, when these plants sprout before other forage plants, or after that period, when some forage plants dry (Vasconcelos et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been also associated with cardiac fibrosis in bovines (Albuquerque et al 2014). The results of this trial show that, at least in animals that show clinical signs of poisoning and recovered, this plant poisoning may cause embryonic deaths and abortions.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, in this study, sudden death was reproduced with the administration of N. stannea to a sheep. In addition to these factors, other plants that cause sudden death, such as Palicourea marcgravii (Tokarnia & Döbereiner 1986) and Albuquerque et al 2014, pubiflora (Becker et al 2013), which cause poisoning in the Midwest Region of Brazil, were not found during the inspection of the pastures. Using photo identification, none of the respondents recognized Palicourea marcgravii, but Amorimia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty in controlling and eradicating some species of Malpighiaceae such as A. pubiflora (Becker et al 2013), A. rigida and A. septentrionalis is a common characteristic of these plants (Tokarnia et al 2012, Albuquerque et al 2014, which may be related to the fact that they have a deep root system that facilitates regrowth. The economic impact of the control of this disease related to the consumption of N. stannea cannot be calculated as there is no accurate information on the cost to reform pastures, of labor and the purchase of pesticides.…”
Section: Discussionmentioning
confidence: 99%